2021
DOI: 10.2196/29058
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach for Mortality Prediction in COVID-19 Pneumonia: Development and Evaluation of the Piacenza Score

Abstract: Background Several models have been developed to predict mortality in patients with COVID-19 pneumonia, but only a few have demonstrated enough discriminatory capacity. Machine learning algorithms represent a novel approach for the data-driven prediction of clinical outcomes with advantages over statistical modeling. Objective We aimed to develop a machine learning–based score—the Piacenza score—for 30-day mortality prediction in patients with COVID-19 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 25 publications
5
38
0
Order By: Relevance
“…In all these cases, an ML model approximates a trained physician’s diagnosis with high accuracy [ 11 , 32 ]. ML can assist intensive care specialists in early detection of patient’s shock and septic conditions, including COVID-19 infections [ 33 ]. Epidemiologists may use ML forecasting capabilities in order to assess the spread of pandemics [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In all these cases, an ML model approximates a trained physician’s diagnosis with high accuracy [ 11 , 32 ]. ML can assist intensive care specialists in early detection of patient’s shock and septic conditions, including COVID-19 infections [ 33 ]. Epidemiologists may use ML forecasting capabilities in order to assess the spread of pandemics [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies focused on environmental measures; acquisition and sharing of knowledge in the general population and among clinicians; development and management of drugs and vaccines; remote psychological support of patients; remote monitoring, diagnosis, and follow-up; and maximization and rationalization of human and material resources in the hospital environment. The study described in [ 27 ] showed that AI-based scores with a purely data-driven selection of features are feasible and effective for the prediction of mortality among patients with COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The three illustrated potentials [ 25 , 26 , 27 ] are also important in DP. In fact, in DP, the need for categorizing images merges with the need to make decisions and/or deduce approaches through actions on large databases and data sets or with other needs not based on medical images [ 1 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first COVID-19-specific scores were developed in China [43,44] 44,45 , uring the first wave of the pandemic. Further scores for prediction of COVID outcomes were later developed all over the world [12,45,46] 12,46,47 , and data from more heterogeneous datasets were collected in order to reduce potential selection bias stemming from sampling from a restricted population of subjects. A case in point is represented by the 4C score, developed by Knight et al [12] 12 : such a score has quickly become popular due to its vast derivation and validation cohorts and its ease of use.…”
Section: Alternative Clinical Scoresmentioning
confidence: 99%